Ab initio study of the magnetic order of some Gadolinium based compounds [ - Zakri, Abismail; Bentria, Bachir (Université Amar Telidji - Laghouat - Département des sciences de la matière, 2018)
The main purpose of our study is to predict the magnetic ordering in some binary gadolinium based compounds, namely; GdN, GdB2, GdAl2, GdAl. In our calculation we used the pseudo potential method and LSDA, GGA and LSDA+U for Exchange and correlation interactions. Magnetic exchange interactions between first and second-nearest neighbors J1 and J2 respectively are derived from total-energy differences different magnetic configurations, then we used these exchange parameters to predict Curie-Weiss and Neel temperatures within mean field theory. These temperatures are compared with experimental data or others theoretical predictions. GdN, GdB2, GdAl2, GdAl are found to be ferromagnetic.